Educação em saúde e diabetes mellitus: práticas na atenção primária. - Gonçalves, Cristiane Aluiza (2017)
Diabetes mellitus (DM) is one of the most prevalent chronic diseases in the world and its relevance to collective health is associated with high morbidity and mortality and its repercussions on patients' daily lives. As an important chronic condition that challenges the health systems, DM finds in Primary Health Care a privileged scenario for the users care, with a guidance to actions in health promotion. In the interface of these actions, the health education is thought as a way to allocate resources to transform living conditions. However, in spite of the expansion of discourses about health education, their practices didn't reach an expressivity in health services. In this perspective, this study has the objective to characterize the health education actions related to DM in Primary Health Care, with a view to its improvement. This is an exploratory study with a qualitative approach done in a Basic Health Unit of the Southern Region of São Paulo Municipality. The data survey was done with the health professionals who work in the care of people with DM. Data were collected through a semi-structured interview and analyzed using the content analysis. The results indicate contradictions and ambivalences about the conceptions and practices of health education of the professionals, related to the coexistence of the traditional model of education combined with elements of the dialogical model. The main difficulties to adopt a participatory education model were related to the low participation and disposal of users to adhere to the guidelines; to the team integration and to the work management. With a view to the exercise of the educational practices, involving the surpass of transmissive and fragmented teaching, anchored in the biomedical reference, the study alerts to the relevance of the specific preparation of professionals in the scope of educational innovation. So, the incentive of permanent education and interprofissional work constitute the new horizons for the renovation of the health education practices in Primary Health Care.